Integrated Reporting and Group Decision-Making for Sustainable Development: A Bibliometric Review - Cunha, Carlos; Duncan, Luis (European Journal of Sustainable Development, 2024)
The demands of society are constantly evolving, imposing significant pressures on business organizations within the context of sustainable development policy. As a result, organizations have begun to move towards promoting information disclosure through integrated reporting, transitioning from sustainability reports to financial reports. Simultaneously, decisions made to address specific problems are no longer the sole responsibility of a single individual. Challenges now revolve around group decision-making with the aim of achieving a consensus solution. To comprehend the landscape of integrated reporting and group decision-making in the scientific literature concerning sustainable development, a bibliometric review was conducted across major scientific databases from 2008 to 2023. The analysis utilized Bibliometrix, based on the R language, and Biblioshiny for graphic generation. The results indicate a quantitative increase in publications addressing integrated reporting and group decision-making in the context of sustainable development. However, a thematic isolation among existing studies was evident, pointing to an opportunity for future research to bridge the gap and establish more robust connections between the subjects. Keywords: integrated reporting, group decision-making, sustainable development, bibliometric review